2011
DOI: 10.1158/0008-5472.can-10-3143
|View full text |Cite
|
Sign up to set email alerts
|

CXCL12/CXCR4 Blockade Induces Multimodal Antitumor Effects That Prolong Survival in an Immunocompetent Mouse Model of Ovarian Cancer

Abstract: The chemokine CXCL12 and its receptor CXCR4 are expressed widely in human cancers including ovarian cancer, where they are associated with disease progression at the levels of tumor cell proliferation, invasion, and angiogenesis. Here we used an immunocompetent mouse model of intraperitoneal papillary epithelial ovarian cancer to demonstrate that modulation of the CXCL12/CXCR4 axis in ovarian cancer has multimodal effects on tumor pathogenesis associated with induction of antitumor immunity. siRNA-mediated kno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
184
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(195 citation statements)
references
References 48 publications
7
184
4
Order By: Relevance
“…Interestingly, previous studies implicated the importance of other chemokine ligand-receptor interactions, such as CXCL12-CXCR4, CX 3 CL1-CX 3 CR1, and CXCL16-CXCR6, in progression and metastasis of ovarian carcinoma (8,34,(42)(43)(44). Current study on the role of XCL1-XCR1 emphasizes the complexity and importance of the chemokine ligand-receptor interactions in the peritoneal milieu of ovarian carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previous studies implicated the importance of other chemokine ligand-receptor interactions, such as CXCL12-CXCR4, CX 3 CL1-CX 3 CR1, and CXCL16-CXCR6, in progression and metastasis of ovarian carcinoma (8,34,(42)(43)(44). Current study on the role of XCL1-XCR1 emphasizes the complexity and importance of the chemokine ligand-receptor interactions in the peritoneal milieu of ovarian carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence also implicates CXCR4 in the proliferation of various cancer cells including ovarian, glioma, melanoma, lung, renal, and thyroid cancer cells [23,24]. The CXCL12/CXCR4 axis delivers surviving signals to hepatoma, ovarian, and chronic leukemia cells and CXCR4 blockade induces the apoptosis of these malignant cells [16,25,26] (Figure 1). CXCL12 expression correlates well with lower apoptosis in human myelodysplastic syndrome [27].…”
Section: Direct Effects On Cancer Cellsmentioning
confidence: 99%
“…Furthermore, a significant correlation has been shown between CXCR4 expression in both primary and metastatic ovarian tumours, as well as lymph node metastases (Jiang et al 2006). In a mouse model of ovarian cancer, siRNA-mediated silencing of CXCL12 reduced tumour growth in vivo, and a CXCR4 antagonist (AMD3100) could increase T-cell-mediated anti-tumour responses (Righi et al 2011). Human primary ovarian tumour cells also express CXCL12 and VEGF following exposure to the hypoxic tumour microenvironment (Kryczek et al 2005).…”
Section: Direct Involvement Of the Elr K Chemokine Cxcl12 In Metastatmentioning
confidence: 99%
“…In two separate studies involving mouse models of EOC, AMD3100 (a clinically approved CXCR4 inhibitor) significantly reduced ovarian cancer cell growth (Ray et al 2011, Righi et al 2011. In mice, administration of AMD3100 significantly reduced intraperitoneal dissemination and angiogenesis (measured by vessel density with the tumour), increased T-cell-mediated anti-tumour immune responses and apoptosis and reduced FoxP3 C T reg cell numbers within the tumour (Righi et al 2011). Subsequently, it was shown that AMD3100 blocked CXCL12/CXCR4 binding, resulting in prolonged survival and reduced tumour growth in mice with disseminated ovarian cancer (Ray et al 2011).…”
Section: Chemokines As Future Therapeutic Targets For Eocmentioning
confidence: 99%